Acoustic indices perform better when applied at ecologically meaningful time and frequency scales. Issue 3 (10th November 2020) - Metcalf, Oliver C.; Barlow, Jos; Devenish, Christian; Marsden, Stuart; Berenguer, Erika; Lees, Alexander C.
Abstract: Acoustic indices are increasingly employed in the analysis of soundscapes to ascertain biodiversity value. However, conflicting results and lack of consensus on best practices for their usage has hindered their application in conservation and land‐use management contexts. Here we propose that the sensitivity of acoustic indices to ecological change and fidelity of acoustic indices to ecological communities are negatively impacted by signal masking. Signal masking can occur when acoustic responses of taxa sensitive to the effect of interest are masked by less‐sensitive acoustic groups, or target taxa sonification is masked by non‐target noise. We argue that by calculating acoustic indices at ecologically appropriate time and frequency bins, masking effects can be reduced and the efficacy of indices increased. We test this on a large acoustic dataset collected in Eastern Amazonia spanning a disturbance gradient of undisturbed, logged, burned, logged‐and‐burned and secondary forests. We calculated values for two acoustic indices: the Acoustic Complexity Index and the Bioacoustic Index, across the entire frequency spectrum (0–22.1 kHz), and four narrower subsets of the frequency spectrum; at dawn, day, dusk and night. We show that signal masking has a large impact on the sensitivity of acoustic indices to forest disturbance classes. Calculating acoustic indices at a range of narrower time–frequency bins substantially increases the classification accuracy of forest classes by random forest models. Furthermore, signal masking led to misleading correlations, including spurious inverse correlations, between biodiversity indicator metrics and acoustic index values compared to correlations derived from manual sampling of the audio data. Consequently, we recommend that acoustic indices are calculated either at a range of time and frequency bins, or at a single narrow bin, predetermined by a priori ecological understanding of the soundscape. Abstrata: Índices acústicos são cada vez mais utilizados em análises de paisagens sonoras para entender padrões de biodiversidade. Entretanto, sua aplicação em biologia da conservação e em contextos de manejo do uso do solo têm sido atrasada devido a resultados conflitantes e a uma falta de consenso sobre as melhores práticas a serem empregadas. Aqui nós propomos que a sensibilidade de índices acústicos em capturar mudanças ecológicas, assim como a fidelidade com que índices acústicos capturam comunidades ecológicas, são severamente impactados por mascaramento do sinal. O mascaramento do sinal pode ocorrer quando respostas acústicas sensíveis aos efeitos que estão sendo monitorados são mascaradas por outros grupos menos sensíveis ou quando a vocalização do taxa alvo dos estudos é mascarado por barulho de outros taxa. Nós argumentamos que ao calcular índices acústicos em intervalos apropriados de tempo e frequência, efeitos mascaradores podem ser reduzidos e a eficácia dos índices acústicos aumentada. Nós testamos isso em um vasto grupo de dados acústicos coletados na Amazônia oriental, abrangendo um gradiente de distúrbios antrópicos, incluindo florestas primárias não perturbadas e aquelas afetadas por extração madeireira, incêndios florestais, extração madeireira e incêndios, assim como florestas secundárias. Nós calculamos os valores de dois índices acústicos, o Índice de Complexidade Acústica e o Índice Bioacústico. Para isso, empregamos todo o espectro de frequências (0–22.1kHz) e quatro subgrupos menores do espectro de frequências: o amanhecer, o dia, o anoitecer e a noite. Nós mostramos que o mascaramento do sinal tem um grande impacto na sensibilidade dos índices acústicos a distúrbios florestais. Calculando índices acústicos em um intervalo menor de tempo‐frequência aumentou substancialmente a acurácia da classificação das classes florestais por modelos do tipo Random Forest. Além disso, o mascaramento do sinal levou a correlações errôneas, incluindo correlações negativas espúrias entre métricas de biodiversidade e valores de índices acústicos, quando comparados com correlações geradas a partir de amostragem manual dos dados de áudio. Consequentemente, nós recomendamos que índices acústicos sejam calculados em intervalos de tempo e frequência menores, pré‐determinados por conhecimento ecológico a priori da paisagem sonora.